Complementary hemispheric lateralization of language and social processing in the human brain - Rajimehr, Reza; Firoozi, Arsalan; Rafipoor, Hossein; Abbasi, Nooshin; Duncan, John (Cell reports (Cambridge), 2022)
Humans have a unique ability to use language for social communication. The neural architecture for language comprehension and production may have prominently emerged in the brain areas that were originally involved in social cognition. Here, we directly tested the fundamental link between language and social processing using functional magnetic resonance data (MRI) data from over 1,000 human subjects. Cortical activations in language and social tasks showed a striking similarity with a complementary hemispheric lateralization. Within core language areas, left-lateralized activations in the language task were mirrored by right-lateralized activations in the social task. Outside these areas, the activations were left lateralized in both tasks, perhaps indicating multimodal integration of social and semantic information. Our findings could have important implications in understanding neurocognitive mechanisms of social disorders such as autism. [Display omitted] •Cortical activation maps in language and social tasks show a striking similarity•Language and social activations are lateralized to left and right brain, respectively•Homologs of language areas in the right hemisphere are involved in social processing•Outside the language network, a left-hemisphere dominance is seen in both tasks Rajimehr et al. demonstrate a relationship between language and social processing in the brain. While language areas are typically found in the left hemisphere, their homologs in the right hemisphere are involved in social processing. The results have implications for understanding how the cortical language network has evolved in humans.